Inserting problem-specific knowledge in multirecombined evolutionary algorithms - Pandolfi, Daniel (2002)
In the restricted single-machine common due date problem the goal is to find a schedule for the n jobs which jointly minimizes the sum of earliness and tardiness penalties, while for the weighted tardiness problem the goal is to find a schedule that minimizes the tardiness penalties. Both problems, even in theirs simplest formulations, are an NP-Hard optimization problem. This presentation discusses how problem specific knowledge is inserted into the evolutionary algorithm to enhance its performance.